Alpha-fetoprotein surge following high-dose chemotherapy in germ cell tumours. (1st April 2013) - Luca Burgio, Salvatore; Menna, Cecilia; Papiani, Giorgio; Casadei Gardini, Andrea; De Luigi, Nicoletta; Corsi, Roberto; Rosti, Giovanni
Abstract : In patients with non-seminomatous germ cell tumours (NSGCTs) who receive chemotherapy and have residual disease, a persistently elevated serum marker level after induction chemotherapy indicates active and progressive disease. High-dose chemotherapy (HDCT) is the standard treatment for patients with relapsed NSGCT. We present a case of a patient with residual disease from NSGCT who showed an increase in serum alpha-fetoprotein levels after HDCT, mimicking progression. Resection of the mass did not show viable cells in the tumour specimen, thus suggesting that the elevated level of the marker was expression of hepatic reconstitution after drug-induced liver damage. HDCT is increasingly used in cases of relapsed NSGCT, and the possibility of treatment-induced alpha-fetoprotein elevation must be taken into account in patient management.